2016
DOI: 10.1159/000441966
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Increased Frequency of Hemodialysis on Volume-Related Outcomes: A Secondary Analysis of the Frequent Hemodialysis Network Trials

Abstract: In previous reports of the Frequent Hemodialysis Network trials, frequent hemodialysis (HD) reduced extracellular fluid (ECF) and left ventricular mass (LVM), with more pronounced effects observed among patients with low urine volume (UVol). We analyzed the effect of frequent HD on interdialytic weight gain (IDWG) and a time-integrated estimate of ECF load (TIFL). We also explored whether volume and sodium loading contributed to the change in LVM over the study period. Treatment effects on volume parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
2
45
0
1
Order By: Relevance
“…Hypothetically, PH in ESKD may be caused by increased right‐sided volume, elevated vascular resistance or both. Multiple studies have shown the effect of more frequent hemodialysis on the amelioration of overall time averaged volume control . In addition, our group has also demonstrated improved brachial artery responsiveness, reduction in systemic vascular resistance, and restored abnormal vascular smooth muscle cell biology by nocturnal home hemodialysis .…”
Section: Discussionmentioning
confidence: 55%
“…Hypothetically, PH in ESKD may be caused by increased right‐sided volume, elevated vascular resistance or both. Multiple studies have shown the effect of more frequent hemodialysis on the amelioration of overall time averaged volume control . In addition, our group has also demonstrated improved brachial artery responsiveness, reduction in systemic vascular resistance, and restored abnormal vascular smooth muscle cell biology by nocturnal home hemodialysis .…”
Section: Discussionmentioning
confidence: 55%
“…It is more likely that changes in left ventricular mass are the result of changes in extracellular fluid volume status rather than changes in β2‐M or other uremic toxin concentrations especially over a relatively short period of time. Another secondary analysis of the FHN trials supports this contention . Furthermore, amyloid deposition in the joints of dialyzed patients takes several years to develop .…”
Section: Discussionmentioning
confidence: 98%
“…Remarkably, a post hoc analysis carried out by the Frequent Hemodialysis Network trial showed that the improvement in left ventricular mass observed in cases of more frequent dialysis was likely caused by extracellular volume reduction directly and not only via an effect on blood pressure [67]. …”
Section: Management Of Fluid Overloadmentioning
confidence: 99%